2019
DOI: 10.1074/jbc.ra119.007625
|View full text |Cite
|
Sign up to set email alerts
|

Mature osteoclast–derived apoptotic bodies promote osteogenic differentiation via RANKL-mediated reverse signaling

Abstract: Edited by Xiao-Fan Wang In bone remodeling, after a lifespan of ϳ2 weeks, osteoclasts undergo apoptosis in each bone turnover cycle, resulting in generation of a large number of apoptotic bodies (ABs). However, the biological roles of osteoclast-derived ABs (OC-ABs) in bone remodeling have not been investigated and remain unknown. In this study, we stimulated bone marrow macrophages with receptor activator of NF-B ligand (RANKL) to obtain both preosteoclasts and mature osteoclasts (mOCs). We then used alendron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…This local apoptosis-induced proliferation is pivotal to sustain tissue-wide cell number and epithelial homeostasis. Similarly, mature osteoclast-derived ApoBDs also promoted viability and differentiation in preosteoblastic cells, reportedly through receptor activator of NF-κB (RANK)-mediated PI3K/Akt/mTOR/protein S6 kinase signalling for survival and osteoblast differentiation [47]. Together these findings not only uncover the key roles of ApoBDs in both locally and distantly regulating tissue homeostasis, but also highlight the potential of stem cell-derived ApoBD treatment as a novel regenerative therapy.…”
Section: Apobd-based Regenerative Therapiesmentioning
confidence: 74%
See 3 more Smart Citations
“…This local apoptosis-induced proliferation is pivotal to sustain tissue-wide cell number and epithelial homeostasis. Similarly, mature osteoclast-derived ApoBDs also promoted viability and differentiation in preosteoblastic cells, reportedly through receptor activator of NF-κB (RANK)-mediated PI3K/Akt/mTOR/protein S6 kinase signalling for survival and osteoblast differentiation [47]. Together these findings not only uncover the key roles of ApoBDs in both locally and distantly regulating tissue homeostasis, but also highlight the potential of stem cell-derived ApoBD treatment as a novel regenerative therapy.…”
Section: Apobd-based Regenerative Therapiesmentioning
confidence: 74%
“…However, from available literature, one could infer and anticipate the emerging potential of developing ApoBDs as a therapeutic delivery vehicle. In the previously mentioned studies, ApoBDs were shown to transfer different molecules (DNA, miRNA and protein) and effectively regulating various aspects of the phagocytosed/recipient cells [46][47][48][49][50]. Other studies have also reported the efficiency of ApoBD contents in mounting cellular responses such as vascular protection and cell migration [51,52].…”
Section: Apobds As a Drug Delivery Platformmentioning
confidence: 94%
See 2 more Smart Citations
“…ApoBDs also mediate intercellular communication between osteoclasts and osteoblasts. In bone remodeling, mature osteoclast-derived ApoBDs (mOC-ApoBDs) are taken up by pre-osteoblastic cells and prompt osteogenic differentiation by activating phosphoinositide 3-kinase (PI3K)/AKT Ser–Thr kinase (AKT) signaling ( Ma et al, 2019 ; Table 1 and Figure 2 ). Moreover, previous studies suggested that osteocyte-derived ApoBDs could recruit the osteoclasts and initiate local bone resorption ( Yuan et al, 2018 ), suggesting that ApoBDs derived from different sources play distinct roles in bone remodeling.…”
Section: The Function Of Apoptotic Extracellular Vesicles In Tissue Rmentioning
confidence: 99%